Correction to: High burden of undernutrition among primary school-aged children and its determinant factors in Ethiopia; a systematic review and meta-analysis - Moges Agazhe Assemie; Alehegn Aderaw Alamneh; Daniel Bekele Ketema; Ali Mekonen Adem; Melaku Desta; Pammla Petrucka; Mekdes Marew Ambaw (BMC, 2020)
An amendment to this paper has been published and can be accessed via the original article.